A Case Report on Necrotizing Fasciitis Due to Multidrug-Resistant Pseudomonas aeruginosa in an Elderly Patient from South India: Highlighting Economic Burden and Treatment Inaccessibility - M, Balaji; R, Sowmya; M, SriPriya; V, Suji; S, Swetha; Dhivyaprasath, P (Indian Journal of Pharmacy Practice, 2026)
The report emphasizes on the case of necrotizing fasciitis with multi-drug-resistant Pseudomonas aeruginosa. A 70-year-old male admitted with lower limb swelling and pus discharge was later diagnosed with necrotizing fasciitis. The patient developed multiple comorbidities on subsequent days, limiting treatment options due to antimicrobial resistance, financial constraints and poor nutritional intake. This case underscores the emerging threat of MDR gram-negative pathogens in severe soft tissue infections, increased hospital stays, prolonged ICU admissions, and treatment inaccessibility for patients in low- and middle-income countries; and the need for antimicrobial stewardship.
Keywords: Antimicrobial drug resistance; Case report; Cost of illness; LRINEC score; Necrotizing; fasciitis